Cell-based assays and molecular simulation reveal that the anti-cancer harmine is a specific matrix metalloproteinase-3 (MMP-3) inhibitor. (October 2021) - Chin, Li-Te; Liu, Ke-Wei; Chen, Yi-Han; Hsu, Shu-Ching; Huang, Lin
Graphical abstract: The interaction of harmine and MMP-3. Schematic green dotted line indicates N2 as the Zinc ion acceptor, hydrogen bond between Glu202 and harmine in cyan and violet Dotted line denotes the interaction of pi- electron cloud over an aromatic group and electron group of the alkyl group. The amino acid sequence of S1′ pocket is labeled and numbered in blue. (replotted from from E MacColl and RA Khalil (2015) Matrix Metalloproteinases as Regulators of Vein Structure and Function: Implications in Chronic Venous Disease, J Pharmacol Exp Ther, 355(3): 410–428; DOI:https://doi.org/10.1124/jpet.115.227330 to accommodate harmine with permission). Highlights: Harmine is a biological β-carboline alkaloid, which attenuates malignant responses in vitro and in vivo animal models, mainly from herbal sources. MMP-3 has been implicated in tumorigenesis, metastasis, and invasion of various cancers. Harmine has very little or no effect on MMP-3 production but inhibits the MMP-3 activity in a dose-dependent manner. Immunoassays and molecular docking indicate harmine is a specific MMP-3 inhibitor. Abstract: The biological activities of harmine have been a much clearer picture in recent years, which include anti-tumor, anti-inflammation and cytotoxic properties. Numerous in vitro and in vivo animal models have confirmed its activities, but its mode of action remains a relative unsolved issue. We therefore investigated harmine for its effects on MMP-3 and the molecular interaction was also simulated. The human glioma cancer cell line, U-87 MG cells, was subjected to different concentrations (1–10 μM) of harmine for 24 h. Methylthiazol tetrazolium (MTT) test, half maximal inhibitory concentration (IC50), western blot analysis, enzyme-linked immunosorbent assay and molecular docking through BIOVIA DiscoveryStudio™ were performed. These results showed that although harmine stimulation in vitro has very little or no effects on MMP-3 expression by U-87 MG cells, the treatment of harmine decreases MMP-3 activity in a dose dependent manner. It was further calculated that 7.9 μM is the IC50 towards MMP-3. Using a molecular dynamic simulation approach, we identified the N2, methyl of C1 and benzene ring of harmine interact with Zn 2+ (2.4 Å), His205 (2.4 Å) and His211 (2.4 Å) as well as Val163 (2.7 Å) at the active site of MMP-3, respectively, and thus conferred a striking specific binding advantage. Taken altogether, the present study evidences that harmine acts as an MMP-3 inhibitor specially targeting the enzymatic active site and possibly efficiently ameliorates MMP-3-driven malignant and inflammatory diseases.